Antibiotic and Duration of Perioperative Prophylaxis Predicts Surgical Site Infection in Head and Neck Surgery. (1st March 2016) - Langerman, Alexander; Thisted, Ronald; Hohmann, Samuel; Howell, Michael
Abstract : Objective: To examine the effect of giving antibiotics on the day of surgery (DOS) vs DOS and first postoperative day (DOS+1) for prophylaxis against surgical site infection (SSI) in clean‐contaminated head and neck surgery (CCHNS). Study Design: Retrospective multi‐institution analysis using University HealthSystem Consortium data. Methods: A multivariate logistic regression model of 8836 discharge records from patients undergoing CCHNS was used to determine the odds of SSI for antibiotic agent/duration combinations. Setting: Ninety‐two academic and affiliated medical centers from 2008 to 2011. Results: Ampicillin/sulbactam, clindamycin, cefazolin + metronidazole, and cefazolin alone were the most common antibiotics. For patients receiving antibiotics only on DOS, there was no significant difference in odds of SSI based on antibiotic choice. When given on the DOS and DOS+1, patients receiving ampicillin/sulbactam had a reduction in odds of SSI by over two‐thirds (odds ratio [OR], 0.28 [95% confidence interval, 0.13‐0.61], P =. 001, compared with ampicillin/sulbactam on DOS only), whereas this effect was not seen with clindamycin (1.82 [0.93‐3.56], P =. 078, compared with clindamycin on DOS only). Prolonging clindamycin beyond the DOS was associated with a higher odds of SSI compared with DOS‐only ampicillin/sulbactam (OR, 2.66; 95% CI, 1.33‐5.30; P =. 006). These relationships held in a subset of physicians and hospitals that used multiple different regimens. DOS+1 regimens were not associated with an increased odds of antibiotic‐induced complications. Conclusion: Prolonging ampicillin/sulbactam beyond the day of surgery may have a protective effect against SSI, and 1 or more days of ampicillin/sulbactam may be preferable to multiple days of clindamycin. New randomized trials are needed to define the ideal regimen for CCHNS.